Analisys of thermal processes during induction surfacing - E. I. Marukovich; V. A. Kharkov; D. A. Meshkov; A. M. Kovalev; I. O. Sazonenko; G. V. Komissarov (Литьë и металлургия, 2020)
Aspects of thermal phenomena associated with the production process of bimetallic billets in conditions of small penetration depths of eddy currents compared to the size of the heated body are considered. Various conditions of heat distribution in the heated layer and its removal are modeled using differentiated thermal resistance. Based on the analysis of the temperature distribution in various situational variants, promising ways to improve this technology are identified.